Fatores determinantes do desempenho financeiro das fintechs de crédito brasileiras - Jayne Luiza Ferreira Sena (2024)
The last decade has seen exponential growth in digital innovation in the financial market, driven by the emergence of fintechs. These innovative companies offer disruptive business models that promise greater flexibility, security and efficiency, offering consumers more advantageous alternatives to traditional financial institutions. Among the various factors that contribute to the success of fintechs, financial performance stands out as one of the main elements that guarantee their expansion and sustainability in the market. The main objective of this study is to analyze the determining factors of the financial performance of credit fintechs in Brazil between 2019 and 2022. To this end, the research was based on a sample of 82 companies categorized by the Central Bank as Direct Credit Companies (SCD) and People-to-People Lending Companies (SEP). The analysis employed dynamic panel econometric models, using the Generalized Method of Moments (GMM) method, to identify the variables that influence the performance of fintechs. The main variables that had a positive impact on fintechs' return on total assets (ROA) were debt, liquidity and the ratio of third-party capital to equity. On the other hand, the COVID-19 pandemic period had a negative influence on ROA. In the case of return on equity (ROE), the ratio of revenue to total assets was positive, while operating efficiency and bad debts had a negative impact. Net interest margin (NIM) was also negatively influenced by operating efficiency and bad debts. Fintechs stand out for their flexible capital structure and focus on technology to reduce costs. They serve specific niches in the financial market and face fewer regulations, making it easier to enter the market. Despite the potential for growth and profitability, efficient debt management is crucial for success in the sector, as evidenced by this pioneering research in the Brazilian context.